Perancangan Sistem Pencatatan Laporan Keuangan Dan Perpajakan Sederhana Berbasis Excel Untuk Efisiensi Biaya Produksi Pada UMKM Pempek Edi - Hartih Shandra Wati (Journal of Applied Accounting And Business, 2026)
Micro,Small,andMediumEnterprises(MSMEs)playanimportantrolein the Indonesian economy; however, many MSME owners still face challenges in financial management and tax compliance due to unstructured transaction recording. This study aims to design a Microsoft Excel–based model for financial and taxation transaction recording as a solution to improve financialmanagement at Buket Caca MSME. This research employs applied research with a qualitative descriptive approach, in which data are collected through observation, interviews, and documentation. The designed model includes daily transaction recording, financial statement preparation, and automaticcalculation of the 0.5% Final Income Tax (PPh Final) for MSMEs. The results show that the Excel-based recording model is able to assist MSME owners in recording transactions in a more organized and structured manner, generating accurate financial and tax information, and improving the efficiency of financial management as well as tax compliance.